Pembatasan Yudisial dan Perluasan Kewenangan Mahkamah Konstitusi dalam Memutus Sengketa Hasil Pilkada - Hantoro, Bimo Fajar (Universitas Airlangga, 2024)
AbstractThe Constitutional Court in Decision Number 85/PUU-XX/2022 stated that the authority to decide regional head election result dispute is the Constitutional Court's original authority. This decision represents a shift from the Court's position in Decision Number 97/PUU-XI/2013, which stated that the Court's authority to settle regional head election result disputes is temporary. The purpose of this study is to examine Decision Number 85/PUU-XX/2022 according to the concept of judicial restraint. This is a juridical-normative research, employing statutory, case, conceptual, and historical approaches. The data used are primary and secondary legal materials. The findings of the study point to two major conclusions. First, there is a dynamic in the regulation of the authority to decide regional head election result dispute. This dynamic occurs as a result of the Court's inconsistent interpretation of the position of regional head elections in the electoral regime, the Court's authority, and the extent of legislators' lawmaking authority. Second, from the standpoint of judicial restraint, the Constitutional Court Decision Number 85/PUU-XX/2022 cannot be justified because of three main considerations: (1) the constitutional limits of Court's authority based on textual, grammatical, and historical interpretations; (2) the ambiguity and variability of interpretations of the Court's authorities under the 1945 Constitution; and (3) separation of powers and institutional limitations of the Constitutional Court.Keywords: Judicial Restraint; Constitutional Court; Regional Head Election Dispute. Abstrak Pasca Putusan MK Nomor 85/PUU-XX/2022, Mahkamah Konstitusi menyatakan kewenangan memutus sengketa hasil pemilihan kepala daerah sebagai kewenangan asli dari Mahkamah Konstitusi. Putusan tersebut merupakan bentuk pergeseran pendirian Mahkamah Konstitusi dalam Putusan MK Nomor 97/PUU-XI/2013 yang menyatakan kewenangan Mahkamah Konstitusi memutus sengketa hasil pilkada sebagai kewenangan yang bersifat sementara. Penelitian ini bertujuan untuk mengkaji Putusan MK Nomor 85/PUU-XX/2022 dari sudut pandang pembatasan yudisial. Penelitian ini bersifat yuridis-normatif dengan menggunakan pendekatan perundang-undangan, pendekatan kasus, pendekatan konseptual, dan pendekatan historis. Data yang digunakan berupa bahan hukum primer dan sekunder. Hasil penelitian menghasilkan dua kesimpulan. Pertama, bahwa terdapat dinamika pengaturan kewenangan penyelesaian sengketa hasil pilkada. Dinamika tersebut terjadi karena inkonsistensi penafsiran Mahkamah Konstitusi dalam memaknai letak pilkada dalam rezim pemilihan, kewenangan Mahkamah Konstitusi, dan luas kewenangan mengatur pembentuk undang-undang. Kedua, dalam sudut pandang pembatasan yudisial, Putusan MK Nomor 85/PUU-XX/2022 tidak dapat dijustifikasi karena tiga pertimbangan utama, yaitu: (1) batasan kewenangan konstitusional Mahkamah Konstitusi berdasarkan penafsiran tekstual, gramatikal, dan historis; (2) kekaburan dan keragaman penafsiran terhadap norma UUD NRI 1945 mengenai kewenangan sengketa hasil pilkada; dan (3) pemisahan kekuasaan dan batasan institusional Mahkamah Konstitusi.Kata Kunci: Pembatasan Yudisial; Mahkamah Konstitusi; Sengketa Hasil Pilkada.